Pigmented eccrine Poroma: dermoscopic and confocal features - Caterina Bombonato; Simonetta Piana; Elvira Moscarella; Aimilios Lallas; Giuseppe Argenziano; Caterina Longo (Mattioli1885, 2016)
Eccrine poroma is a rare benign adnexal tumor of epithelial cells originating from the terminal ductal portion of the sweat glands that is typically located on palms and soles, although other cutaneous sites can be affected [1]. It is usually nonpigmented even if there is a pigmented variant that corresponds to 17% of cases and it is usually underdiagnosed, since it is mistakenly confused with other pigmented tumors [2,3]. Dermoscopy and reflectance confocal microscopy (RCM) may assist in the correct diagnosis of this tumor. Herein, we report one case of pigmented eccrine poroma (PEP) that simulated clinically a cutaneous melanoma or a basal cell carcinoma. Dermoscopy and RCM excluded the possibilities of those two diagnoses; the overall confocal findings were suggestive for a benign epithelial tumor. Histology was fundamental to diagnose this lesion as a pigmented eccrine poroma. Even if the diagnosis of eccrine poroma remains histopathological still, as in this case report, noninvasive tools such as dermoscopy and RCM examinations can be of help to rule out the diagnosis of melanoma. Larger studies on this rare pigmented variant of eccrine poroma could shed new light on the identification of specific diagnostic dermoscopic and confocal features.